Survey of A. Gučas activity and researches - Bagdonas, A.; Butkienė, G.; Lapė, J.; Rimkutė, E. (Psichologija, 1989)
The article provides a detailed overview of A. Gučas' activities and research, as well as a bibliography.
Keywords: A. Gučas; research; biography; bibliography